Association of hyperuricemia with coronary heart disease and other cardiovascular outcomes: A systematic review and dose-response meta-analysis - Diyang Lyu; Rui Zhuang; Jiaqi Li; Yucen Wu; Yiming Di; Meifen Song; Liyong Ma; Jingen Li; Yong Zhang (PLoS ONE, 2025)
Introduction Uric acid (UA) is considered as a potential risk factor for coronary heart disease (CHD) and other cardiovascular diseases (CVDs). However, the association between hyperuricemia and the risk of CHD and other cardiovascular outcomes has not been fully clarified. This systematic review and dose-response meta-analysis was conducted to comprehensively the association between hyperuricemia and the risk of CHD or other cardiovascular outcomes in the general population. Methods We systematically searched Medline, Cochrane Library, Embase, and two clinical trial registration databases from inception to June 30, 2025, without restrictions on language or publication status. Only cohort and case-control studies enrolling participants without CHD, other CVDs, or gout at baseline were included. The primary outcome was the association between hyperuricemia and the risk of CHD, and secondary outcomes were the association between hyperuricemia and the risk of fatal and nonfatal CVDs, included CHD death, CVD, CVD death, and myocardial infarction (MI). Risk of bias was assessed using the Risk Of Bias In Non-randomized Studies-of Exposure (ROBINS-E) tool. All statistical analyses were performed using R 4.4.2. We conducted meta-analyses, heterogeneity assessments, publication bias tests, trim-and-fill analyses, subgroup and sensitivity analyses, meta-regressions, and dose-response meta-analyses. The GRADE recommendation was used to evaluate the quality of evidence. Results A total of 42 articles representing 39 individual studies and 1,082,880 participants were included. Among these, 2 articles were assess as “very high risk of bias”, eight as “high risk of bias”, and two as “some concerns”. Hyperuricemia was significantly associated with an increased risk of CHD [HR 1.21 (95%CI 1.14–1.28), p < 0.001, I2 = 34.34%], CHD death [1.20 (1.05–1.36), p = 0.005, I2 = 41.28%], CVD death [1.75 (1.12–2.74), p = 0.014, I2 = 49.48%], and MI [1.23 (1.03–1.47), p = 0.025, I2 = 56.96%]. No significant association was observed for overall CVD risk [1.09 (0.94–1.27), p = 0.245, I2 = 0%]. For each unit increase in serum UA, the risk of CHD, CHD death, CVD, CVD death, and MI increased by 16%, 13%, 12%, 11%, and 7%, respectively. No factors with a significant impact on the results were identified through subgroup analyses or meta-regression. Sex may have a potential influence, but the results were not robust. Further dose-response meta-analysis revealed a linear relationship between higher serum UA and CVD risk, and a U-shaped association between serum UA and CVD mortality in men. The quality of evidence was rated as low for CHD and very low for the other cardiovascular outcomes. Conclusion This systematic review and dose-response meta-analysis provides low- to very-low-quality evidence suggesting that hyperuricemia may be associated with an increased risk of CHD and other fatal or nonfatal CVDs. Trial registration This study was registered in PROSPERO CRD42024538553.